Biomarkers of ALI/ARDS: Pathogenesis, Discovery, and Relevance to Clinical Trials - Janz, David R.; Ware, Lorraine B. (Seminars in Respiratory and Critical Care Medicine, 2013)
Despite the high incidence and poor prognosis of acute lung injury (ALI) and the acute respiratory distress syndrome (ARDS), it remains challenging to identify patients who are at highest risk of developing these syndromes, differentiate these syndromes from other causes of acute respiratory failure, and accurately prognosticate once the diagnosis is made. The identification and validation of biological markers of ALI has the potential to ameliorate these challenges by facilitating studies of therapies aimed at prevention, identifying patients more accurately that have ALI so they can benefit from evidence-based therapies and enrollment in clinical trials, and determining which patients are unlikely to have a positive outcome to guide therapeutic choices and trials of experimental rescue therapies. This article reviews the current state of biomarker research in ALI/ARDS. New methodologies for identification of novel biomarkers of ALI, including metabolomics, proteomics, gene expression, and genetic studies are also discussed.
Keywords: acute lung injury; biomarker; metabolomics; proteomics; genomics; genetics; acute respiratory distress syndrome